Influencing Holistic Health Policy - Erica Bell (The Scientific World Journal)
Beliefs that health policy-making is an inherently ‘ideological’ or ‘irrational’ process appear to have worked to prevent researchers from developing better understandings of the kind of evidence that does work to influence policy. Without a model of policy-making that positions policy decision-makers as capable of being informed by specific forms of evidence that speak to policy contexts, it is difficult for research to begin to shape health policy. Recent years have seen the development of a research industry that focuses on developing and describing research approaches for shaping health and social services policy. This analysis paper offers a highly selective overview of generic features of policy-relevant research for holistic health. It aims to support efforts to develop better evidence for health policy by exploring elements of the genre of policy-relevant research, particularly as it applies to the challenges of holistic health policy-making. First, it offers a conceptual definition of holistic health policy-making, as well as research evidence for this kind of policy making, identifying some of the generic features of policy-relevant research. Second, it outlines some of the key practices for delivering sound evidence for health policy, in ways that highlight the salient differences between doing research for holistic health policy, and doing academic research in health. The paper concludes with directions for developing better evidence for holistic health policy-making that question the assumptions of quality which often inform elite funding agencies, calling for their diversification.